Analisis Faktor Internal dan Eksternal dalam Keberhasilan Pemberian ASI Eksklusif - Annisa Nurhayati Hidayat; Sri Rahayu; Antika Maulida Rahayu (Universitas Faletehan, 2026)
Exclusive breastfeeding serves as a critical measure to mitigate infant mortality and morbidity rates, yet its implementation frequently falls short of national benchmarks in various districts. This study intended to examine both internal and external determinants of exclusive breastfeeding success. Employing a quantitative approach, this research utilized a cross-sectional framework and was conducted in Cilegon, Banten Province, Indonesia. A sample size of 298 breastfeeding mothers with infants aged 6–12 months was gathered via purposive sampling. Validated and reliable questionnaires were distributed for data collection. The statistical processing involved univariate and bivariate (chi-square). The outcome demonstrated that a large proportion of participants (88.9%) achieved exclusive breastfeeding practices. Significant correlations were identified regarding maternal psychological readiness (p=0.000), motivational levels (p=0.016), midwife guidance (p=0.000), family reinforcement (p=0.001), exposure to relevant information (p=0.009), and socio-cultural factors (p=0.000) with breastfeeding outcomes. Therefore, strengthening education and assistance from health workers and families is highly recommended to maximize this program.